2019
DOI: 10.1200/jco.2019.37.15_suppl.9008
|View full text |Cite
|
Sign up to set email alerts
|

Clinical activity and tolerability of BLU-667, a highly potent and selective RET inhibitor, in patients (pts) with advanced RET-fusion+ non-small cell lung cancer (NSCLC).

Abstract: 9008 Background: RET fusions are targetable oncogenic drivers in up to 2% of NSCLC, yet no selective RET inhibitors are approved. BLU-667 is an investigational highly potent and selective RET inhibitor targeting oncogenic RET alterations, including those that confer resistance to multikinase inhibitors (MKIs). We provide an update on the registration-enabling ARROW study (NCT03037385) of BLU-667 in pts with RET-fusion+ NSCLC. Methods: The global ARROW study includes DE (30-600 mg daily [QD or BID]) and dose e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
90
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 0 publications
1
90
0
Order By: Relevance
“…Thus, recent therapeutic targeting of these cancers has shifted to RET-specific inhibition. Recently, RET-specific inhibitors BLU-667 and LOXO-292 have been investigated and preliminary clinical data suggest that they may be effective anticancer agents in patients with NSCLC and other cancers harboring RET translocations [29][30][31][32]. Subbiah et al reported anticancer activity in 2 patients with KIF5B-RET fusions where both patients showed a PR after 16 weeks of treatment with BLU-667 at doses of 200-300 mg/d [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, recent therapeutic targeting of these cancers has shifted to RET-specific inhibition. Recently, RET-specific inhibitors BLU-667 and LOXO-292 have been investigated and preliminary clinical data suggest that they may be effective anticancer agents in patients with NSCLC and other cancers harboring RET translocations [29][30][31][32]. Subbiah et al reported anticancer activity in 2 patients with KIF5B-RET fusions where both patients showed a PR after 16 weeks of treatment with BLU-667 at doses of 200-300 mg/d [29].…”
Section: Discussionmentioning
confidence: 99%
“…Subbiah et al reported anticancer activity in 2 patients with KIF5B-RET fusions where both patients showed a PR after 16 weeks of treatment with BLU-667 at doses of 200-300 mg/d [29]. In the ARROW study, BLU-667 demonstrated potent antitumor activity and was well tolerated in patients with RET fusion-positive NSCLC [32]. Of the 79 patients enrolled, 44 had KIF5B-RET and 16 had CCDC6-RET fusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gainor et al presented preliminary efficacy data with the RET inhibitor BLU-667 [7]. BLU-667 was explored in a dose-escalation study that resulted in a maximum tolerated dose of 400 mg per day.…”
Section: Ret-fusion: Selective Ret Inhibitors Show Durable Responsesmentioning
confidence: 99%
“…Publisher's Note Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations 7. For latest news from international oncology congresses see: http://www.springermedizin.at/ memo-inoncology…”
mentioning
confidence: 99%